The diagnostic challenge in pulmonary tumour embolism in cancer: a case report and literature review - Zielińska, Aleksandra; Braun, Marcin; Piasecka, Dominika; Minc, Piotr; Romańska, Hanna M. (Contemporary Oncology/Współczesna Onkologia, 2020)
Pulmonary tumour embolism is a rare condition without specific symptoms or pathognomonic features. Pulmonary tumour embolism can occur as the first manifestation of cancer, but because of diagnostic difficulties, it is often wrongly recognised as a more common cardiopulmonary disease. We present a case of a 46-year-old Caucasian male with no prior malignancy diagnosis, admitted because of progressing dyspnoea and cough. Based on radiological and clinical presentations, sarcoidosis, silicosis and lymphangitic carcinomatosis were considered in the differential diagnosis. Histopathological analysis of lung biopsy revealed that multiple emboli of atypical epithelial cells found in the pulmonary vessels were of gastrointestinal origin. Further pathological examination of the gastric biopsy led to the final diagnosis of the signet-ring cells gastric adenocarcinoma. The patient was referred for chemotherapy. After a short-term partial remission, he died within two months after the final diagnosis. The presented case illustrates challenges posed by the diagnostic process of pulmonary tumour embolism.